2019
DOI: 10.4037/aacnacc2019436
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Critical Care Nurse in Disclosing Difficult News

Abstract: S usan is a nurse in the medical intensive care unit. For the past 3 days, she has cared for Ms B, a 59-year-old woman admitted with pelvic pain. Ms B was transferred to the medical intensive care unit because of hemodynamic instability after vaginal blood loss. She has undergone diagnostic tests and has a new diagnosis of uterine cancer. Ms B retains decision-making capacity but is critically ill and decisions need to be made about her treatment. Ms B has not yet been told her cancer diagnosis because she spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 28 publications
(55 reference statements)
0
13
0
Order By: Relevance
“…Thus, only ten met the study criteria; they are presented on table 1. (8,11,18,(19)(20)(21)(22)(23)(24)(25) The analysis of the studies included in this review allowed us to identify three main points addressed in the articles. The first is about the little or no communication skills developed during nurses' training, a situation described in all articles analyzed.…”
Section: ❚ Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, only ten met the study criteria; they are presented on table 1. (8,11,18,(19)(20)(21)(22)(23)(24)(25) The analysis of the studies included in this review allowed us to identify three main points addressed in the articles. The first is about the little or no communication skills developed during nurses' training, a situation described in all articles analyzed.…”
Section: ❚ Resultsmentioning
confidence: 99%
“…The second point discussed is about how the disclosure of bad news appears during nurses' practice, from primary to tertiary care. (8,11,19,21,25) Finally, another aspect identified is the creation of the link between patient/ family/nurse for an effective communication of bad news, (22,23) as well as for strengthening the trust between them in difficult moments. (8,(18)(19)(20)(21)(22)(23)(24)(25) Regarding the communication skills of students and nursing professionals in general, the studies showed that, during undergraduate course or technical training, there are no subjects or courses addressing this issue, and, consequently, this produces a deficit in the development of professional skills.…”
Section: ❚ Resultsmentioning
confidence: 99%
“…Usually, it is the medical team who disclose difficult news to patients and their families. However, nurses who work at the bedside are fully involved in this activity because they spend more time with the patient and often know the details of the needs of both the patients and the families 7 …”
Section: Protocol Objective Strategy Example Of Practical Application Of the Spikes Protocol In The Context Of Covid‐19mentioning
confidence: 99%
“…However, nurses who work at the bedside are fully involved in this activity because they spend more time with the patient and often know the details of the needs of both the patients and the families. 7 Nurses help families in many instances during the process of communicating bad news; for example, following up conversations to clarify technical terms and jargon, ensuring understanding of difficult information or clarifying the implications of the diagnosis or potential treatments. In addition, families may have a preference for conversations with nurses because of their proximity in the nurse-familypatient relationship and the fragility of the relationship with other professionals from the team.…”
mentioning
confidence: 99%
See 1 more Smart Citation